2020
DOI: 10.1038/s41467-020-15457-9
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-wide association of gut microbiome features for schizophrenia

Abstract: Evidence is mounting that the gut-brain axis plays an important role in mental diseases fueling mechanistic investigations to provide a basis for future targeted interventions. However, shotgun metagenomic data from treatment-naïve patients are scarce hampering comprehensive analyses of the complex interaction between the gut microbiota and the brain. Here we explore the fecal microbiome based on 90 medication-free schizophrenia patients and 81 controls and identify a microbial species classifier distinguishin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
191
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(215 citation statements)
references
References 74 publications
2
191
2
5
Order By: Relevance
“…Our findings regarding community-level differences in microbiota composition is consistent with previous studies in schizophrenia Shen et al, 2018;Zheng et al, 2019;Zhu et al, 2020). Beta-diversity findings are further reinforced by random forests analysis, which revealed that microbial taxa can predict patients with schizophrenia from NCs with 0.82 AUC.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings regarding community-level differences in microbiota composition is consistent with previous studies in schizophrenia Shen et al, 2018;Zheng et al, 2019;Zhu et al, 2020). Beta-diversity findings are further reinforced by random forests analysis, which revealed that microbial taxa can predict patients with schizophrenia from NCs with 0.82 AUC.…”
Section: Discussionsupporting
confidence: 92%
“…One Streptococcus sp. identified by the model has previously been implicated in social behavior deficits, by altering neurotransmitter levels in peripheral tissues in recipient mice (Zhu et al 2020). This taxon feature is found to be positively associated with age.…”
Section: Neurological Activities In Agingmentioning
confidence: 82%
“…The role of gut microbiome in neuro-generative processes is increasingly evident and the perturbation of the microbiome and microbial products have been demonstrated to affect behavior (Hsaio et al 2013) through the gut-brain axis . Studies have reported differences in short-chain fatty acids synthesis, tryptophan metabolism, and synthesis/degradation of neurotransmitters to be associated with neurological and social problems (Zhu et al 2020). Abnormalities of neurotransmitter systems, especially the aberrations of neuronal signaling involving dopamine, glutamate, and γ-aminobutyric acid (GABA) are among the pathways known to be dysregulated in diseases like Schizophrenia (Zhu et al 2020).…”
Section: Neurological Activities In Agingmentioning
confidence: 99%
“…They have profound impact on human health, being associated with a broad range of human diseases including cancers, diabetes, schizophrenia and autoimmunue diseases etc. [9][10][11][12]. However, there are a few exceptions such as placenta, amniotic fluids and cerebrospinal fluids (CSF) where no microbiome is found (amniotic fluids and placenta) [13,14] or known (CSF).…”
Section: Introductionmentioning
confidence: 99%